Techno-economic analysis of the transition from off-Grid to on-grid electricity in the mining industry - Nurliani, Alin; Noveria, Ana (Universitas Widya Mataram, 2025)
The mining sector's reliance on off-grid diesel generators imposes significant economic and environmental costs, including high energy expenditures and substantial greenhouse gas emissions. While existing techno-economic studies have explored renewable hybrids for off-grid mining operations, there remains a critical gap in evaluating grid-connected transitions—especially in emerging economies with coal-dependent grids like Indonesia. This study aims to find out how can transitioning from diesel to grid electricity in Indonesia’s mining sector achieve cost savings and emission reduction. Through integrated Levelized Cost of Electricity (LCOE), Net Present Value (NPV), and CO₂ emission analysis of a mining company as a case study, we demonstrate two key novel contributions: (1) a framework for quantifying trade-offs between cost savings and emission reductions in coal-reliant grids, and (2) empirical evidence that grid adoption reduces energy costs by 66% (from 0.50/kWh to 0.17/kWh) while delivering a projected NPV of 14.46 million (IRR: 32.34%). Moreover, switching to on-grid PLN shows a potential emission reduction of 2,054 tons/year (15% decrease). These findings highlight the dual imperative of grid electrification and renewable integration for sustainable mining, offering policymakers and industry stakeholders a replicable model to balance economic and environmental goals in resource-intensive sectors.